The Protective Role of Resveratrol against Arsenic Trioxide-Induced Cardiotoxicity. (14th November 2013) - Zhang, Weiqian; Guo, Changming; Gao, Ruifeng; Ge, Ming; Zhu, Yanzhu; Zhang, Zhigang
Abstract : Arsenic trioxide (As2 O3 ) shows substantial anticancer activity in patients with acute promyelocytic leukemia (APL). Unfortunately, limiting the application of this effective agent to APL patients is severe cardiotoxicity. Resveratrol, the natural food-derived polyphenolic compound, is well known for its antioxidant properties and protects the cardiovascular system. But the potential role of resveratrol against As2 O3 in heart via nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) is unclear. The present study evaluated the effects of pretreatment with resveratrol and As2 O3 on oxidative stress and cardiac dysfunction in rat. In the present study, resveratrol decreased As2 O3 -induced reactive oxygen species generation, oxidative DNA damage, and pathological alterations. In addition, cardiac dysfunction parameters, intracellular calcium and arsenic accumulation, glutathione redox ratio, and cAMP deficiency levels were observed in As2 O3 -treated rats; these changes were attenuated by resveratrol. Furthermore, resveratrol significantly prohibited the downregulation of both Nrf2 and HO-1 gene expressions that were downregulated by As2 O3, whereas resveratrol did not alter As2 O3 -induced nitric oxide formation. Thus, the protective role of resveratrol against As2 O3 -induced cardiotoxicity is implemented by the maintenance of redox homeostasis (Nrf2-HO-1 pathway) and facilitating arsenic efflux. Our findings suggest coadministration with resveratrol, and As2 O3 might provide a novel therapeutic strategy for APL.